ChemInform Abstract: Low‐Temperature Topochemical Transformation of Bi13Pt3I7 into the New Layered Honeycomb Metal Bi12Pt3I5. Issue 13 (March 2015) - Kaiser, Martin; Rasche, Bertold; Isaeva, Anna; Ruck, Michael
Abstract Single crystals of Bi13Pt3I7 (prepared from a mixture of H2 treated Bi, Pt, and BiI3 at 380 °C for 6 d).